Effectiveness of Self-Instructional Modules: Enhancing Student Independence with Clear Guides, Interactive Materials, and Continuous Evaluation - Wulandari, I Gusti Agung Ayu; Esaputra, I Nyoman Tri; Yudiana, I Kadek Edi (International Journal of Research in Counseling and Education, 2024)
SIM is a learning method designed to enable students to learn independently with the help of systematically arranged modules. In this study, we emphasize the importance of meeting three main requirements for SIM to function properly, namely: (1) clear instructions in each learning activity, (2) interactive presentation materials, and (3) use of permit values in each learning activity. This study aims to activate the effectiveness of the Self-Instructional Module (SIM) in training student independence. The research method used is a quantitative method with an experimental design. This study involved two groups of students, namely the experimental group using SIM and the control group using conventional learning methods. Data collection was carried out through independent learning tests and material understanding before and after the intervention. Data analysis was carried out using a t-test to see significant differences between the two groups. The results of the study showed that SIM that meets these three requirements can significantly increase student independence. Students who use SIM with clear instructions, interactive materials, and ongoing evaluations show increased independent learning and material understanding. In conclusion, effective implementation of SIM can be an innovative solution in improving the quality of students' independent learning.